Computer Aided Design of Polygalacturonase II from aspergillus niger - Noorbatcha, Ibrahim Ali; Ismail, Nur Izzah; Mohd. Salleh, Hamzah (IIUM Press, 2011)
ABSTRACT: Pectin is a complex polysaccharide found in the cell walls of plants and consisting mainly of esterified D-galacturonic acid resides in -(1-4) chain. In production of fruit juice, pectin contributes to fruit juice viscosity, thereby reducing the juice production and increasing the filtration time. Polygalacturonase improves the juice production process by rapid degradation of pectin. In this project we have designed a novel polygalacturonase enzyme using computer aided design approaches. The three dimension structure of polygalacturonase is first modeled on the basis of the known crystal structure. The active site in this enzyme is identified by manual and automated docking methods. Lamarckian genetic algorithm is used for automated docking and the active site is validated by comparing with existing experimental data. This is followed by in silico mutations of the enzymes and the automated docking process is repeated using the mutant enzymes. The strength of the binding of the ligands inside the active site is evaluated by computing the binding score using Potential Mean Force (PMF) method. The in silico mutations R256Q and K258N are found to decrease the binding strength of the ligand at the active site, indicating lowering of enzyme activity, which is consistent with the experimental results. Hence in silico mutations can be used to design new polygalacturonase enzymes with improved enzyme activity.